Answer:
We just need to evaluate and get f(2i)=0, f(-2i)=0.
Explanation:
Since
, then
, and we can apply this when we evaluate
for 2i and -2i.
First we have:
![f(2i) =(2i)^3 + 4(2i)=2^3i^3+8i=8(-i)+8i=0](https://img.qammunity.org/2020/formulas/mathematics/college/f9ac6vmyksfoxnj5zianpwpwscffqdiayj.png)
Which shows that 2i is a zero of f(x).
Then we have:
![f(-2i) =(-2i)^3 + 4(-2i)=(-2)^3i^3-8i=-8(-i)-8i=8i-8i=0](https://img.qammunity.org/2020/formulas/mathematics/college/fjwrkv54grhy86w55ay50ca6mtax5yqsbt.png)
Which shows that -2i is a zero of f(x).